The lack of parental help among adult children in Finland - Majamaa, Karoliina (Economics and Business Review, 2014)
The main focus of this paper is on adult children who do not receive any practical help or financial support from own parents. The perspective is two-folded: the lack of help is considered both from the potential givers' (parents') and from the potential receivers' (adult children's) points of view. The results indicate that the lack of financial support is more common than the lack of practical help, whereas received practical help extends beyond the early years of adulthood. According to the binominal logistic regression analyses, the lack of parental help is most evident when there is no need, in the other words, financial support is less probably received after graduation and with good incomes, whereas practical help is received especially after having children. Lack of regular contacts between parent and adult child and long geographical distance seem also be detrimental to parental helping. Furthermore, there was some interplay between an adult child's disadvantaged position and a lack of parental support. If scarce resources of both parent and adult child interplay with lack of help, social problems may arise more easily, in other words, the lack of help accumulates more or less to certain families.(original abstract)